Does muscle strength predict working memory? A cross-sectional fNIRS study in older adults - Cai, Zhidong; Wang, Xing; Wang, Qiang (Frontiers in Aging Neuroscience, 2023)
Objective: Previous research has primarily focused on the association between muscle strength and global cognitive function in older adults, while the connection between muscle strength and advanced cognitive function such as inhibition and working memory (WM) remains unclear. This study aimed to investigate the relationship among muscle strength, WM, and task-related cortex hemodynamics. Methods: We recruited eighty-one older adults. Muscle strength was measured using a grip and lower limb strength protocol. We measured the WM performance by using reaction time (RT) and accuracy (ACC) in the N-back task and the cortical hemodynamics of the prefrontal cortex (PFC) by functional near-infrared spectroscopy(fNIRS). Results: We found positive correlations between grip strength (P＜0.05), 30-second sit-up (P＜0.05) and ACC, negative correlation between grip strength (P＜0.05) and RT. Furthermore, we observed positive correlations between grip strength and the level of oxygenated hemoglobin (HbO2) in dorsolateral prefrontal cortex, frontopolar area, ventrolateral prefrontal cortex (P＜0.05), and negative correlations between grip strength and the level of deoxygenated hemoglobin (Hb) in left dorsolateral prefrontal cortex, frontopolar area, left ventrolateral prefrontal cortex (P＜0.05). Additionally, we noticed positive correlations between RT and the level of Hb in left dorsolateral prefrontal cortex, right frontopolar area (P＜0.05), and negative correlations between RT and the level of HbO¬2 in left dorsolateral prefrontal cortex, frontopolar area (P＜0.05). However, the cortical hemodynamics did not mediate the relationship between muscle strength and WM performance (RT, ACC). Conclusion: The grip strength of older adults predicted WM in the cross-section study. The level of hemodynamics in PFC can serve as a predictor of WM.